2021
DOI: 10.1089/jwh.2020.8863
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Maternal Mortality Within a Global Context: Historical Trends, Current State, and Future Directions

Abstract: In the United States, despite significant investment and the efforts of multiple maternal health stakeholders, maternal mortality (MM) has reemerged since 1987 and MM disparity has persisted since 1935. This article provides a review of the U.S. MM trajectory throughout its history up to its current state. From this longitudinal perspective, MM trends and themes are evaluated within a global context in an effort to understand the problems and contributing factors. This article describes domestic and worldwide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 39 publications
0
43
0
Order By: Relevance
“…Maternal and infant mortality rates in the United States (U.S.) constitute an important public health problem, because these rates surpass those in similarly large, developed, and wealthy countries, and are characterized by stark disparities for people of color, underserved rural residents, and those of a low socioeconomic status. For example, although the global maternal mortality ratio (MMR) has decreased by 45% over the last three decades (385 per 100,000 live births in 1990 to 211 in 2017), the U.S. MMR (calculated as the number of maternal deaths per 100,000 live births) has increased by 58% (12 in 1990 to 19 in 2017) [1]. Every year, about 700 U.S. women die due to pregnancy and its complications [2].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal and infant mortality rates in the United States (U.S.) constitute an important public health problem, because these rates surpass those in similarly large, developed, and wealthy countries, and are characterized by stark disparities for people of color, underserved rural residents, and those of a low socioeconomic status. For example, although the global maternal mortality ratio (MMR) has decreased by 45% over the last three decades (385 per 100,000 live births in 1990 to 211 in 2017), the U.S. MMR (calculated as the number of maternal deaths per 100,000 live births) has increased by 58% (12 in 1990 to 19 in 2017) [1]. Every year, about 700 U.S. women die due to pregnancy and its complications [2].…”
Section: Introductionmentioning
confidence: 99%
“…2 The maternal mortality rate in the United States has increased by 58% since 1990, a time during which 157 of 183 countries in a World Health Organization study reported significant declines in maternal death. 3 , 4 Meanwhile, large racial, ethnic, socioeconomic, and geographic disparities persist. For example, African American women are more than thrice as likely to die from pregnancy and childbirth as White women, a gap that has not narrowed in decades.…”
Section: Introductionmentioning
confidence: 99%
“…WHSs were important guarantees to improve women’s health, and in the context of achieving the SDGs’ target. It is necessary to provide suitable services with increased attention, coordination and integration at the government level [ 78 ].…”
Section: Discussionmentioning
confidence: 99%